Fiscal Transfer Redistribution and Regional Inequality between Island and Non-Island Provinces in Indonesia - Ahmad, Abdul Chalid; Effendi, Nuri; Budiono, Budiono; Hadiyanto, Ferry (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The allocation of fiscal transfer funds to archipelagic provinces is currently still smaller than non-archipelagic provinces in Indonesia. Its ocean area is larger than that of non-island provinces, and vice versa. Meanwhile, the allocation determination is still based on land area. This study aims to analyze the determinant variables of fiscal transfer disparities between the two groups of provinces, simulate island fiscal transfer funds (DTFK), and analyze their impact on regional inequality. This research uses a panel data model, involving 8 island provinces and 24 non-island provinces, during 2008-2017. This research period was adapted to the 2017 Islands Regional Bill. The results of the DTFK simulation contributed to increasing the DAU, DAK, and DBH of the island provinces. In effect, DAK and DBH reduce regional inequality, while DAU does not.